Smartphone non-users experience disproportionately higher psychological distress than their counterparts: Mediations via psychosocial resources in a large sample of college students in China - Xin, Meiqi; Mo, Phoenix Kit han; Li, Jibin; Liu, Xi; Jiang, Hong; Chen, Yonghua; Ma, Le; Lau, Joseph Tak fai (Journal of affective disorders, 2022)
•Around 56.8% of smartphone non-users had probable depression.•Smartphone non-users had significantly higher depression and loneliness than their user counterparts.•Based on the conservation of resources theory, lower social support, high-quality peer relationship, and self-esteem are potential mechanisms underlying the negative effects of smartphone non-use on depression/loneliness.•Digital divide in smartphone use/access may drive the disparities in population's mental health. Despite growing adoption of digital technologies, the gap between users and non-users (aka digital divide) persists. It is imperative to determine whether and how such a gap can lead to disparities in mental health outcomes among populations. However, few empirical studies have explored the effect of smartphone non-use on psychological well-being. A large-scale cross-sectional survey was conducted among 26,951 college students in Shaanxi Province, China. Levels of depression and loneliness were first compared between smartphone non-users and their user counterparts. Based on the Conservation of Resources theory, structural equation modeling was then used to test the mediating roles of social support, quality of peer relationship, and self-esteem. Around 56.8% of smartphone non-users had probable depression and they reported significantly higher depressive symptoms (Cohen's d = 0.52) and loneliness (Cohen's d = 0.30) than users. The hypothesized mediation model was well supported with good model fit. Lower levels of social support, quality of peer relationship, and self-esteem fully mediated the total effect of smartphone non-use status on loneliness and explained 69.4% of the total effect on depression. Findings might be subject to self-reporting bias and limitations due to a cross-sectional design. The study adds new evidence that the minority group of smartphone non-users exhibited disproportionately greater psychological distress than users resulting from lower supportive social relationships and positive sense of self. The findings inform the future investigation into digital divide in smartphone use/access and its negative impact on population's psychological well-being.